Physico Chemical Properties and the Antinutrient status of a non-Alcoholic Beverage (Coke) - JO Akaninwor; MO Wegwu; EO Nwaichi (Journal of Applied Sciences and Environmental Management, 2010)
The physicochemical properties and the antinutrient status of the beverage, coke were evaluated to determine its suitability for consumption and toxic levels in mammal. The mean levels of nitrates, total nitrogen, chloride, ammonia, tannin, cyanogenic glycosides and caffeine in the samples were (mg/l): 0.008 ± 0.001, 150.000 ±3.446, 11.000 ± 0.686, 183.000 ± 3.019, 0.016 ±5.976, 0.020 ± 0.010 and 0.146 ± 0.002 respectively. The pH of the samples gave a mean value of 3.500, while the mean metal concentrations gave (mg/l) - 0.990 ± 0.099 (Mg); 38.030 ±0.050 (Na); 1.400 ±0.114 (Fe); 0.650 ± 0.014 (Zn); 0.080 ± 0.005 (Mn); 4.720 ± 0.016 (K) and 10.120 ± 0.094 (Ca). Toxicological test using whister albino Rats, shows that the beverage was relatively safe. Generally, the results shows that the antinutrient status of the beverage fell within the standards adopted by most countries. Similarly, the other parameters fell within natural background level although few fell above WHO specifications.